Design and Evaluation of a Virtual Tour–Based Application for the Placement Criteria of the Instrument Landing System (ILS) - Rusman; Moch Rifai; Prayitno, Hadi; Artadarma, Nyoman (ZETROEM, 2026)
The Instrument Landing System (ILS) is a critical component of aviation navigation that ensures aircraft landing accuracy and safety. However, public understanding of restricted ILS areas and equipment placement criteria remains limited, as existing informational media—such as regulatory documents or slide presentations—lack interactivity and spatial visualization. This study aims to design and evaluate a Virtual Tour-based ILS Application as an interactive educational medium to visualize and explain the placement criteria of ILS equipment in a three-dimensional (3D) environment. The research used the ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design model to systematically develop the application. The content and functional design were derived from the Indonesian Civil Aviation Authority’s SKEP/113/VI/2002 and ICAO Annex 10 Volume I standards. Data collection methods included observation, expert validation, and user testing. The application was evaluated using three quality dimensions of the ISO 25010 software standard: functional suitability, compatibility, and usability. Participants included media experts, subject matter experts, and 20 community members residing near Budiarto Airport, Indonesia. As a result, the Virtual ILS application achieved high evaluation scores across all dimensions—functional suitability (97.5%), compatibility (100%), and usability (90.16%)—indicating excellent performance, ease of use, and educational value. The interactive 3D visualization effectively improved users’ comprehension of ILS restricted zones and equipment placement requirements, compared to conventional informational media.